Beyond the annual budget : global experience with medium term expenditure frameworks. (World Bank e-Library., 2012)
What conditions determine the success of Medium Term Expenditure Frameworks (MDTFs)? How should the implementation of MTEFs be sequenced and coordinated with other budget reforms? What role should organizations such as the World Bank, bilateral development partners, and other international agencies play in supporting MTEF adoption? How can country authorities implement a new MTEF or strengthen an existing one?Beyond the Annual Budget provides a comprehensive review of global experience with Medium Term Expenditure Frameworks (MTEFs). Looking at countries both with and without MTEFs over the pe.